Influences of atmospheric humidity on sliding speed characteristics of dry sliding phenomena - Hong, Wei Chee (2023)
The effect of adsorbed water layers in sliding phenomena has been widely recognized, but it has yet to be explained thoroughly after many years of research. Previous researches tend to explain the phenomena from chemical and qualitative viewpoints, thus physical viewpoint approaches with quantitative evidence are necessary to complement the previous research works. Studies were done to estimate the thickness of adsorbed water layers in recent years to obtain quantitative evidence of the effect of adsorbed water layers. It was found that the thickness of the adsorbed water layer derived from atmospheric humidity could provide physical influences on sliding phenomena. The hypothesis in this study based on the Stribeck curve is; the friction coefficient may decrease significantly with the increase of sliding speed at high relative humidity (RH) compared to low RH. To verify the hypothesis, a pair of JIS SUS304 austenitic stainless steel balls were scratched against each other horizontally with a vertical overlapping distance of 80 µm at sliding speeds of 20, 200, and 2000 µm·s−1 in RH of 5, 55, and 95%. The experimental results supported the hypothesis as the friction coefficient for medium to high RH decreased significantly with increasing sliding speed while the friction coefficient decreases slightly at low RH. The friction coefficient decreases significantly at high sliding speed and RH. The possible physical effects of the adsorbed water layers were suggested.